Kepemimpinan Pastoral Pemuda dalam Meneguhkan Pertumbuhan Gereja - Yahya Harmo Malailak; Ebrianus Liwuto (Sekolah Tinggi Teologi Jaffray Jakarta, 2021)
The spiritual formation of a pastor or pastoral leadership is a gift and a callingfrom God to a leader. A leader/pastor can strengthen/guide young people intheir spiritual growth to full maturity. Spiritual guidance for young people isnot as easy as most people think, it is not just a weekly routine of attendingworship and the responsibility as a leader in a church institution is consideredcomplete. In the current context, people who live in cities with a thousand andone complex problems faced every day have their own challenges. Thechallenge for today's youth is technological change and advancement.Therefore, every young woman should get proper and correct guidance andmentoring in order to face this complex life. This complex life needs to betaken seriously by all parties, especially the church, so that young people arenot trapped in a life that ultimately leads them away from God.